2021
DOI: 10.1111/ajr.12705
|View full text |Cite
|
Sign up to set email alerts
|

Five years on: Influences on early career health professionals from a rural interprofessional pre‐registration immersion program

Abstract: Objective To ascertain former students' perceptions of and influences from a final‐year pre‐registration, rurally located, clinically based, 5 week interprofessional program on their subsequent work and career in the health professions. Design Online survey delivered 5 years post‐program (4 years post‐graduation). Setting The Tairāwhiti interprofessional education program was first undertaken in 2012/2013 by students from six health professional degree programs (dentistry, dietetics, medicine, nursing, pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…TIPE students had more positive attitudes to healthcare teams at baseline, but these were controlled for in analytic models. Consistent with other TIPE evaluations, those who attended the TIPE programme reported valuing the experience highly; this may have made them more positive about the impact of the experience on their subsequent careers 23 39…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…TIPE students had more positive attitudes to healthcare teams at baseline, but these were controlled for in analytic models. Consistent with other TIPE evaluations, those who attended the TIPE programme reported valuing the experience highly; this may have made them more positive about the impact of the experience on their subsequent careers 23 39…”
Section: Discussionsupporting
confidence: 68%
“…There is a paucity of studies exploring the effects of pregraduation IPE learning activities during health professionals’ early careers. Postgraduate recollections of preregistration IPE experiences and perceived impacts of IPE on teamwork abilities have been reported previously 39 41 42. Hylin et al found that graduates, who had spent 2 weeks in an interprofessional training ward, had lasting positive and negative impressions of this course and they considered that they promoted teamwork in the workplace 18 months postgraduation 42.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The geographic workforce distribution was also recognised within other work. Both Gleissner 21 (in the context of Speech-Language Therapy) and Pullon et al 27 suggested that geographic workforce distribution was a key contributor to obvious health needs not being met within rural areas. Reid and Dixon 24 quantified this for physiotherapists, where 81% worked in urban areas, citing challenges in the ability to recruit to rural areas.…”
Section: Geographic Workforce Distributionmentioning
confidence: 99%
“…Reid and Dixon 24 quantified this for physiotherapists, where 81% worked in urban areas, citing challenges in the ability to recruit to rural areas. However, Pullon et al 27 suggested that even with a workforce willing and able to practice in rural areas, there is a perceived lack of opportunity for career diversity or progression.…”
Section: Geographic Workforce Distributionmentioning
confidence: 99%